Applied drought modeling, prediction, and mitigation - Senaut, Zekai (Amsterdam : Elsevier, 2015)
Applied Drought Modelling, Prediction, and Mitigation provides a practical guide to new and recent methodologies for drought characterizations, change modeling, down-scaling, and future predictions. The modeling procedures covered by the book include recent advancements in regional drought extent, coverage, intensity, and water deficit predictions, which are increasingly significant given current climate change impacts on water resources. Each modeling procedure is explained theoretically prior to the mathematical derivation, and includes book examples, exercises, and case studies that.
Front Cover; Applied Drought Modeling, Prediction, and Mitigation; Copyright; Table of Contents; Dedication; Preface; Chapter One: Introduction; 1.1. General; 1.2. Historical View; 1.3. Atmospheric Composition and Drought; 1.4. Drought Definitions; 1.5. Droughts, Aridity, and Desertification; 1.6. Drought Impacts; 1.7. Drought Regions; 1.8. Drought Types and Their Impacts; 1.8.1. Meteorological Drought; 1.8.2. Hydrological Drought; 1.8.3. Agricultural Drought; 1.8.4. Socioeconomic Drought; 1.8.5. Famine; 1.8.6. Water Shortages and Effects; 1.9. Significant Drought Mitigation Points.
Includes bibliographical references and index.
Keywords: Droughts; Drought forecasting